ANALISIS PENDERIVASIAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE ( GCG ) DALAM UNDANG-UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Elizabeth Magdalena Aritonang; Bismar Nasution; Mahmul Siregar; Keizerina Devi Azwar (Universitas Sumatera Utara, 2014)
In 2006 NCG Good Corporate Governance issued in the code of corporate governance. GCG the company for two things: the ethics and regulations. Regulations on Limited Liability Companies is Law No. 40 of 2007. This study was conducted to answer the problem of the translation of GCG principles in the Code of GCG issued derivation NCG and the corporate governance principles in the Company Law and the principles of GCG is not enough derivation in the Company Law. This study analyzed agency theory and research methods, descriptive analytical law. Results of this study was the Code of GCG issued by NCG more comprehensive because it contains 5 versions of the OECD principles of corporate governance, transparency, accountability, fairness, responsibility and independence. Further corporate governance principles contained in the NCG and the OECD have derivation the law of norms in the Company Law is the right stakeholders, announcements, CSR, performance accountability through annual reports and financial statements. Last that the whole principle of GCG is not enough derivation well within the norm of law in the Company Law is no specific requirement to the board of directors, board of commissioners, independent directors, not arranged on all company audited, do CSR, company secretary, standards and implementation CSR sanctions, shares with the same par value as well as the dominance of shareholders. Keywords : Derivation, Good Corporate Governance, Law No. 40 of 2007 on Limited Liability Company